PENULISAN KESIMPULAN DAN SARAN DALAM KARYA ILMIAH UNTUK MENINGKATKAN KUALITAS PUBLIKASI AKADEMIK - Haryati, Reti Sri; Hayadi, B, Herawan; Apriyudin, Apriyudin; Nurlina, Nina; SuryoPutra, Muhamad Wachid; Oktalia, Huda (STAI Darul Qalam Tangerang, 2026)
Conclusions and suggestions are an important part of scientific articles that serve as an affirmation of research results as well as recommendations for further research. However, many authors are still less than optimal in compiling these two parts, thus reducing the quality of academic publications. This article aims to examine effective strategies in writing conclusions and suggestions to be more systematic, clear, and impactful. The method used is a literature study of various scientific writing guidelines and indexed articles. The results of the study show that the conclusions must be concise, based on findings, and answer the research objectives, while the suggestions must be specific, applicable, and relevant to the research results. The implementation of the right strategy can increase the credibility and competitiveness of academic publications.